Strengthening Early Education Literacy Culture through the Utilization of Reading and Writing Corners in Carangwulung Wonosalam Village Jombang Regency - Nur Danyssa Supartono; Fani Oktia Dwi Handini; Intan Nur Dalilah; Niken Grah Prihartanti (Yayasan Adra Karima Hubbi, 2024)
Background. Reading is important in the teaching and learning process. Reading is the process of absorbing knowledge through reading or writing. Each student has varying abilities from fast, medium and slow in terms of reading. Purpose. This study aims to improve habituation in students in increasing interest in reading. Method. By holding literacy, it is hoped that it will be able to increase students' interest in reading and increase knowledge that can be a provision in the future in Carangwulung Wonosalam Village. Results. The research subjects were children aged 7-12 years with data collection techniques by direct observation, interviews and documentation. Conclusion. This research can be concluded that the reading corner is very helpful in fostering students' interest in reading in the classroom, the role of the reading corner in growing students' interest in reading, namely, as a place to read facilitator, as the closest reading material, a comfortable reading place and a place to read that attracts attention, so that from some of these roles it helps foster interest in reading.